Pastoral with refugees: answers of the Holy See - Vegliò, Antonio María (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
Since the pontificate of Pius XII, the Holy See, through the pontiffs John XXIII, Paul VI, John Paul II, Benedict XVI and Francis, have been constantly and tirelessly working to defend the rights of refugees, migrants and displaced people, intervening in international forums, with documents, speeches and animation of the concrete charitable activity.